Tigers at twilight / 19. - Osborne, Mary Pope (Magic tree house, 1999)
Having used their magic tree house to travel to India, where they must get a gift to help free the dog Teddy from a spell, Jack and Annie have adventures involving a tiger and other endangered jungle animals.